Cassava: constraints to production and the transfer of biotechnology to African laboratories - Bull, Simon E.; Ndunguru, Joseph; Gruissem, Wilhelm; Beeching, John R.; Vanderschuren, Hervé (Plant cell reports, 2011)
Knowledge and technology transfer to African institutes is an important objective to help achieve the United Nations Millennium Development Goals. Plant biotechnology in particular enables innovative advances in agriculture and industry, offering new prospects to promote the integration and dissemination of improved crops and their derivatives from developing countries into local markets and the global economy. There is also the need to broaden our knowledge and understanding of cassava as a staple food crop. Cassava ( Manihot esculenta Crantz) is a vital source of calories for approximately 500 million people living in developing countries. Unfortunately, it is subject to numerous biotic and abiotic stresses that impact on production, consumption, marketability and also local and country economics. To date, improvements to cassava have been led via conventional plant breeding programmes, but with advances in molecular-assisted breeding and plant biotechnology new tools are being developed to hasten the generation of improved farmer-preferred cultivars. In this review, we report on the current constraints to cassava production and knowledge acquisition in Africa, including a case study discussing the opportunities and challenges of a technology transfer programme established between the Mikocheni Agricultural Research Institute in Tanzania and Europe-based researchers. The establishment of cassava biotechnology platform(s) should promote research capabilities in African institutions and allow scientists autonomy to adapt cassava to suit local agro-ecosystems, ultimately serving to develop a sustainable biotechnology infrastructure in African countries.